PERBANDINGAN STATUS KESEHATAN GIGI DAN MULUT SISWA USIA 12 TAHUN DI SMP XAVERIUS 1 DAN SMPN 39 PALEMBANG - Bertha Aulia; Sri Wahyuni; Rahma Fernita Aprilia (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2019)
World Health Organization (WHO) survey in 2003, 60-90% dental caries experience children in the world. RisetKesehatan Dasar (RISKESDAS) data in 2018, the prevalence of dental and oral problems in South Sumatraprovince was 52,4%. Dental and oral health can be influenced by parent’s education levels, parent’s incomelevels, parent’s occupation, and dietary habit. The purpose of this study was to compare the dental and oralhealth status of 12-year-old students at SMPN 39 and SMP Xaverius 1 Palembang. This was a observationalanalytic study with a cross sectional study design. Samples were all 12-years-old students at SMP Xaverius 1and SMPN 39 Palembang with total 90 students obtained by purposive sampling technique. Parent’s educationlevels, parent’s income levels, parent’s occupation, and dietary habit data were analyzed using Kruskal-Wallisand to compare DMF-T and PBI at SMP Xaverius 1 and SMPN 39 Palembang were using Mann-Whitney test.There are significant differences between parent’s education levels, parent’s income levels, parent’s occupation,and dietary habit on dental and oral health, DMF-T and PBI p=0.000 (p<0.05). The conclusion of this study isthe oral and dental health of 12-years-old students at SMP Xaverius 1 is better than SMPN 39 Palembang.